ERiK-Methodological Report III Conceptualisation and Design of the ERiK-Surveys 2022 - Schacht, Diana D. (wbv Media, 2023)
The ERiK-Methodological Report III is the third in a series of methodological reports related to the "Entwicklung von Rahmenbedingungen in der Kindertagesbetreuung -indikatorengestützte Qualitätsbeobachtung (ERiK)" study. The report focuses on the conception, sample selection, and survey designs of the ERiK-Surveys 2022. Together with the ERiK-Methodological Report I and II, that cover the ERiK Surveys 2020, it provides comprehensive background information on the ERiK-Surveys conducted in 2022 and describes their progression until December 31, 2021. The subsequent steps, such as implementing the ERiK-Surveys 2022, will be described in a later report.